Uncovered Interest Rate Parity and Analysis of Monetary Convergence of Potential EMU Accession Countries - Oliver Holtemöller (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2003)
This paper analyzes deviations from uncovered interest rate parity which are interpreted as indicator of the substitutability of currencies. Backward recursive statistical tests and error correction models are applied to study the co-movement of interest rates, and rolling regressions are used to illustrate size and volatility of country specific risk premia. In accordance to their degree of monetary integration with the Euro area, EU acceding and accession countries are divided into three groups. Additionally, the results show that uncovered interest rate parity is well supported by empirical evidence if it is augmented by a country-specific risk premium.
urn:nbn:de:kobv:11-10050534
Keywords: F36; C32; C22; F41; 330; Cointegration; economic convergence; European monetary union; monetary integration; interest rate parity; Zinsparität; Währungssubstitution; Risikoprämie; EU-Erweiterung; Europäische Wirtschafts- und Währungsunion; Europäische Wirtschafts- und Währungsunion; Schätzung; Schätzung; EU-Staaten; Osteuropa